Gut microbiota: a new player in the pathogenesis of perioperative neurocognitive disorder?. Issue 1 (28th March 2021) - Dong, Liang; Li, Juan; Zhang, Chao; Liu, De‐Xing
Abstract : Perioperative neurocognitive disorder (PND), including postoperative delirium and postoperative cognitive dysfunction (POCD), is a common postoperative complication in elderly patients, who represent an expanding segment of our population. PND is a multifactorial disease resulting in higher morbidity and mortality. The precise mechanism of PND is yet to be fully delineated. Identifying the modifiable risk factors and mechanisms for PND would be an important step forward in preventing such adverse events and thus improving patients' outcomes. It is increasingly recognized that gut microbiota also manifest effects in the central nervous system via the microbiota‐gut‐brain axis, which has emerged as an important player in shaping aspects of behavior and cognitive function. Recent studies have found that patients with cognitive dysfunction after surgery and anesthesia have obvious gut microbiome disorders. These findings are paralleled by a growing body of preclinical investigations aimed at better understanding how surgery and anesthesia affect the central nervous system and possibly contribute to cognitive decline. Here, we present a broad topical review of the literature supporting the role of gut microbiota in PND. We provide an overview of the mechanisms underlying the pathogenesis of PND from pre‐clinical and human studies. Therefore, gut microbiota could be a putative therapeutic target for PND in the future.